SEXISM IN GREEN’S LOOKING FOR ALASKA - Faturrachman Hulalata; Jim R. Tuna; Imelda Lolowang (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study is to reveal the form of sexism representation in the novel Looking for Alaska. This novel raises the issue of sexism against women which is addressed through the character of Alaska and other female characters. The researcher uses qualitative method with the semiotic approach of Roland Barthes. This study aims to determine the form of representation of sexism based on signs and meanings which are analyzed based on the meaning of Denotation, Connotation, and Myths that are formed about sexism in the Novel Looking for Alaska. The object that is the focus of the research consists of 5 dialogues quoted, which show sexist behavior and speech. The results of this study indicate that women are depicted as weak creatures, described as mere sexual objects, women are not smarter than men, women arguments are often considered trivial, used as objects by the media as branding to provoke men's desires, and are also considered to be troublesome for men.